Regulation Of Notarial Authority in the Transfer of Copyright Through Inheritance - Pande Galih Gita Gayatri; Putu Ayu Sriasih Wesna; I.B Gede Agustya Mahaputra (Inovasi Pratama Internasional. Ltd, 2027)
The regulation of notarial authority in the transfer of copyright through inheritance is a crucial issue in Indonesian civil law because copyright has become an intangible economic asset capable of generating royalties and other commercial benefits for heirs. This study analyzes the legal certainty of copyright transfer through inheritance and the appropriate forms of notarial deeds needed to document such transfer. The research applies normative legal research using statutory and conceptual approaches, with primary legal materials consisting of the Indonesian Civil Code, the Copyright Law, and the Notary Office Law. The findings indicate that copyright, particularly its economic rights, transfers by operation of law after the creator dies; however, authentic notarial deeds remain necessary to clarify heirship, identify the inherited copyright object, regulate economic-right management, and support administrative recording at the Directorate General of Intellectual Property. The notary does not determine heir status judicially but provides preventive legal protection through authentic deeds such as deeds of heirship statement, deeds of inheritance distribution, deeds of economic-right management, and deeds of transfer of economic rights. The article concludes that a more explicit technical regulation is required to harmonize copyright, inheritance, and notarial law